Aluminum-based composite material and preparation method thereof

By introducing reinforced particles into the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and adopting a specific preparation process, the problem of insufficient elastic modulus and tensile strength of existing aluminum-based composite materials is solved, and efficient performance improvement is achieved and suitable for high-end applications.

CN119710394APending Publication Date: 2025-03-28CHINALCO RES INST OF SCI & TECH CO LTD +1

Patent Information

Application Number
CN202411812489.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The elastic modulus and tensile strength of existing aluminum-based composite materials are difficult to meet the needs of high-end fields such as aerospace and defense technology.

Method used

By introducing 10% to 25% of reinforced particles, such as SiC, TiC, AlN, ZrB2 and TiB2, into the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, an aluminum-based composite material with high tensile strength and elastic modulus was prepared in combination with vacuum air atomization, discharge plasma sintering, thermal deformation treatment and heat treatment.

Benefits of technology

The tensile strength and elastic modulus of aluminum-based composite materials have been significantly improved, increasing its elastic modulus by 10GPa to 20GPa, achieving a combination of lightweight and high performance, and is suitable for the fields of aerospace and defense science and technology with high standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710394A_ABST
    Figure CN119710394A_ABST
Patent Text Reader

Abstract

The invention provides an aluminum-based composite material and a preparation method thereof. The aluminum-based composite material comprises an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and reinforced particles, wherein the reinforced particles are distributed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix in a dispersed manner; wherein the mass of the reinforcing particles accounts for 10%-25% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, and the reinforcing particles are selected from any one or more of SiC particles, TiC particles, AlN particles, ZrB2 particles and TiB2 particles. According to the aluminum-based composite material, the reinforcing particles are introduced into the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix to serve as a reinforcing phase, the tensile strength and the elastic modulus of the aluminum-based composite material can be improved, the elastic modulus of the aluminum-based composite material is improved by 10 GPa to 20 GPa, and combination of light weight and high performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to an aluminum-based composite material and a preparation method thereof. Background Art

[0002] Lightweight and ultra-high-strength Al-Zn-Mg-Cu alloy is one of the main structural materials widely used in aerospace, national defense science and technology and other fields. Aluminum alloy accounts for more than 70% of the total weight of structural materials on aircraft. With the improvement of industrial level and environmental awareness, energy conservation and emission reduction and fuel consumption reduction are important goals for the development of aerospace structural materials. Therefore, the demand for lightweight aluminum alloy structural materials is increasing. However, the elastic modulus of Al-Zn-Mg-Cu alloy is low, only about 70GPa, which cannot meet the requirements of high specific strength and high specific modulus for aerospace structural materials serving in harsh environments. Metal-based composite materials prepared by adding ceramic particles such as TiB2, SiC, and TiC to the metal matrix have high strength, high modulus and other properties, and have great application prospects in aerospace, national defense science and technology and other fields. TiB2 ceramic particles are widely used as reinforcing phase particles in the preparation of metal-based composite materials because of their advantages of high strength, high elastic modulus, high hardness, high melting point, high chemical stability, and no interface reaction with most metal elements.

[0003] The external addition method and the in-situ endogenous method are the two main methods for preparing TiB2 particle reinforced aluminum-based composites, and each method has its own advantages and disadvantages. The external addition method is to add TiB2 particles to the matrix by smelting or powder metallurgy, which can prepare composite materials with a high volume fraction, but the added particles are large in size and nano-scale particles are easy to agglomerate. The in-situ endogenous method is to directly generate the reinforcing phase particles inside the matrix by designing the chemical reaction between the components, and then obtain the corresponding composite material. The interface bonding strength between the particles and the matrix is ​​high, and nano-scale particles can be generated, but the volume fraction of the generated particles is low, and the performance improvement is limited. Rapid solidification combined with powder metallurgy and thermal mechanical processing is an effective method for preparing TiB2 particle reinforced aluminum-based composites with excellent mechanical properties. The combination of rapid solidification and powder metallurgy can achieve the preparation of uniform fine-grained structure, in which the dispersion uniformity of TiB2 particles can also be guaranteed; while thermal deformation and heating treatment can further regulate the microstructure, control the formation and distribution of nano-scale precipitation phase, and further improve the comprehensive mechanical properties of the composite material.

[0004] The Chinese patent application with the publication number of patent application CN 113755726A discloses a technology for preparing in-situ generated TiB2 particle reinforced Al-Zn-Mg-Cu composite material by combining atomization with hot isostatic pressing, thermoplastic processing and heat treatment. The modulus of the composite material reaches 75-85GPa, the tensile strength is ≥500MPa, and the elongation is ≥8%. The mass fraction of TiB2 in the composite material obtained by this method is below 10wt%. Although the plasticity is maintained, the improvement of the modulus is not obvious. The Chinese patent application with the publication number of patent application CN 114032429A and the Chinese patent application with the publication number of patent application CN 111500908A both disclose the technology of preparing TiB2 particle reinforced aluminum-based composite material by external addition method. The elastic modulus of the composite material is about 73GPa, which is difficult to meet the application requirements in high-end fields such as aerospace, national defense science and technology.

[0005] Obviously, the above-mentioned prior patents have not formed a systematic method that simultaneously includes composite material composition design, organizational regulation, and performance optimization for the preparation of high-strength and high-modulus aluminum-based composite materials, and the resulting composite materials cannot meet the requirements of elastic modulus and tensile strength for composite materials in high-end fields such as aerospace, national defense science and technology. Summary of the invention

[0006] The main purpose of the present invention is to provide an aluminum-based composite material and a preparation method thereof, so as to solve the problem in the prior art that the elastic modulus and tensile strength of the aluminum-based composite material are difficult to meet market demand.

[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided an aluminum-based composite material, which includes an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and reinforcing particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; wherein the mass of the reinforcing particles is 10% to 25% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; in terms of mass percentage, the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix includes 10wt% to 15% of Zn element, 2.4wt% to 3.6wt% of Mg element, 1.0wt% to 1.6wt% of Cu element, 0.1wt% to 0.4wt% of Sc element, 0.1wt% to 0.4wt% of Zr element, and 0.04wt% to 0.1wt% of Er element; wherein the reinforcing particles are selected from any one or more of SiC, TiC, AlN, ZrB2 and TiB2 particles.

[0008] Furthermore, the average grain size of the aluminum-based composite material is 2 to 3 μm.

[0009] Furthermore, at 20-30° C., the tensile strength of the aluminum-based composite material is 750-850 MPa, and / or the elastic modulus of the aluminum-based composite material is 85-95 GPa.

[0010] According to another aspect of the present invention, there is provided a method for preparing the aforementioned aluminum-based composite material, the preparation method comprising: step S1, vacuum gas atomizing Al-reinforced particle intermediate alloy blocks, pure Zn blocks, pure Mg blocks, Al-5Cu intermediate alloy blocks, Al-5Sc intermediate alloy blocks, Al-10Zr intermediate alloy blocks, and Al-5Er intermediate alloy blocks according to the above-mentioned proportions to obtain aluminum-based composite material powder; step S2, spark plasma sintering the aluminum-based composite material powder to obtain an aluminum-based composite material block; step S3, sequentially performing thermal deformation treatment and heat treatment on the composite material block to obtain an aluminum-based composite material; wherein the temperature of the smelting package during the vacuum gas atomization process is 830-860°C.

[0011] Furthermore, in the above step S1, the atomization pressure of the vacuum air atomization is 1.5-8 MPa, and / or the tundish temperature of the vacuum air atomization is 780-820°C, and / or the atomization medium of the vacuum air atomization is argon; and / or the median particle size of the aluminum-based composite material powder is 15-30 μm, the nitrogen content is ≤100 ppm, and the oxygen content is ≤800 ppm.

[0012] Furthermore, in the above step S1, the mass fraction of the reinforced particles in the Al-reinforced particle master alloy block is 28% to 32%, and / or the median particle size of the reinforced particles in the Al-reinforced particle master alloy block is 0.8 to 5 μm.

[0013] Furthermore, in the above step S2, the sintering temperature of spark plasma sintering is 420-550°C; and / or the sintering pressure of spark plasma sintering is 40-50MPa; and / or the holding time of spark plasma sintering is 5-30min; and / or the pulse current of spark plasma sintering is 600-800A.

[0014] Furthermore, in the above step S2, the density of the aluminum-based composite material block is 99.0% to 99.9%.

[0015] Furthermore, in the above step S3, the process of thermal deformation treatment includes: subjecting the aluminum-based composite material block to hot extrusion treatment to obtain a hot extrusion treatment block; wherein the temperature of the hot extrusion treatment is 360 to 420°C, and / or the extrusion speed of the hot extrusion treatment is 0.8 to 2 m / s, and / or the hot extrusion ratio of the hot extrusion treatment is 8:1 to 30:1.

[0016] Furthermore, in the above step S3, the heat treatment process includes: subjecting the hot extruded block to a two-stage solution treatment and an aging treatment in sequence; the two-stage solution treatment includes a primary solution treatment and a secondary solution treatment in sequence; and / or the temperature of the primary solution treatment is 300-400°C, and the time of the primary solution treatment is 4-10h; and / or the temperature of the secondary solution treatment is 460-480°C, and the time of the secondary solution treatment is 0.5-2h; and / or the temperature of the aging treatment is 110-150°C, and the time of the aging treatment is 6-48h.

[0017] By applying the technical solution of the present invention, the aluminum-based composite material of the present application is beneficial to improve the tensile strength and elastic modulus of the aluminum-based composite material by introducing reinforcing particles as reinforcing phases in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, so that the elastic modulus of the aluminum-based composite material is improved by 10GPa to 20GPa, thereby achieving a combination of lightweight and high performance. Specifically, on the one hand, the high melting point and high modulus characteristics of the reinforcing particles, as well as their dispersed distribution inside the matrix grains and at the grain boundaries, effectively inhibit the growth of the matrix grains during thermal deformation and heat treatment, and at the same time, a large number of reinforcing particles hinder the movement of dislocations during deformation, thereby improving the tensile strength (tensile strength is increased to 750MPa to 850MPa) and elastic modulus of the aluminum-based composite material. On the other hand, the addition of Zn elements exceeding the traditional 7xxx series aluminum alloys and trace amounts of Sc, Zr, and Er microalloying elements in the alloy matrix can play the role of grain refinement, recrystallization inhibition, and aging strengthening, thereby significantly improving the comprehensive mechanical properties of the aluminum-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 The present invention shows the organizational structure diagram of the TiB2 particle reinforced aluminum-based composite material powder after aerosol treatment in Example 1 of the present application; wherein (a) represents the surface morphology (secondary electron image) of the TiB2 particle reinforced aluminum-based composite material powder; (b) represents the cross-sectional organizational morphology of the TiB2 particle reinforced aluminum-based composite material powder;

[0020] Figure 2The present invention provides the organizational structure diagram of the TiB2 particle reinforced aluminum-based composite material after thermal deformation and heat treatment in Example 1 of the present application; wherein, (a) represents the hot extrusion organizational morphology (backscattered electron image); (b) represents the hot extrusion organizational orientation distribution diagram (IPF diagram); (c) represents the organizational morphology (backscattered electron image) after solution treatment; (d) represents the precipitate phase distribution diagram in the composite material after aging treatment. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0022] As analyzed in the background technology of this application, there is a problem in the prior art that the elastic modulus and tensile strength of aluminum-based composite materials are difficult to meet market demand. In order to solve the above problem, this application provides an aluminum-based composite material and a preparation method thereof.

[0023] In a typical embodiment of the present application, an aluminum-based composite material is provided, which includes an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and reinforcing particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; wherein the mass of the reinforcing particles is 10% to 25% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; in terms of mass percentage, the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix includes 10wt% to 15% of Zn element, 2.4wt% to 3.6wt% of Mg element, 1.0wt% to 1.6wt% of Cu element, 0.1wt% to 0.4wt% of Sc element, 0.1wt% to 0.4wt% of Zr element, and 0.04wt% to 0.1wt% of Er element; wherein the reinforcing particles are selected from any one or more of SiC, TiC, AlN, ZrB2 and TiB2 particles.

[0024] The aluminum-based composite material of the present application is beneficial to improve the tensile strength and elastic modulus of the aluminum-based composite material by introducing reinforcing particles as reinforcing phases in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, so that the elastic modulus of the aluminum-based composite material is improved by 10GPa to 20GPa, and the combination of lightweight and high performance is achieved. Specifically, on the one hand, the high melting point and high modulus characteristics of the reinforcing particles, as well as their dispersed distribution inside the matrix grains and at the grain boundaries, effectively inhibit the growth of the matrix grains during thermal deformation and heat treatment, and at the same time, a large number of reinforcing particles hinder the movement of dislocations during deformation, thereby improving the tensile strength (tensile strength is increased to 750MPa to 850MPa) and elastic modulus of the aluminum-based composite material. On the other hand, the addition of Zn elements exceeding the traditional 7xxx series aluminum alloy and trace amounts of Sc, Zr, and Er microalloying elements in the alloy matrix can play the role of grain refinement, recrystallization inhibition, and aging strengthening, thereby significantly improving the comprehensive mechanical properties of the aluminum-based composite material.

[0025] In one embodiment of the present application, the average grain size of the aluminum-based composite material is 2-3 μm.

[0026] It is preferred to control the average grain size of the aluminum-based composite material and the average grain size of the equiaxed crystal structure in the aluminum-based composite material within the above range, which is conducive to controlling the microstructure of the aluminum-based composite material, thereby improving its mechanical properties. At the same time, the refinement of the grain size can enhance the material's resistance to crack propagation and reduce stress concentration at the crack tip, thereby improving the tensile strength and toughness of the aluminum-based composite material, thereby improving its application scenarios for withstanding high stress and complex loads.

[0027] In one embodiment of the present application, at 20-30° C., the tensile strength of the aluminum-based composite material is 750-850 MPa, and / or the elastic modulus of the aluminum-based composite material is 85-95 GPa.

[0028] Optimizing and controlling the tensile strength and elastic modulus of the aluminum-based composite material within the above ranges indicates that the aluminum-based composite material has excellent mechanical properties, which is more conducive to its application in technical fields with high standards.

[0029] In another typical embodiment of the present application, a method for preparing an aluminum-based composite material is provided, the preparation method comprising: step S1, vacuum gas atomizing an Al-reinforced particle intermediate alloy block, a pure Zn block, a pure Mg block, an Al-5Cu intermediate alloy block, an Al-5Sc intermediate alloy block, an Al-10Zr intermediate alloy block, and an Al-5Er intermediate alloy block according to the above-mentioned ratio to obtain an aluminum-based composite material powder; step S2, spark plasma sintering the aluminum-based composite material powder to obtain an aluminum-based composite material block; step S3, sequentially performing thermal deformation treatment and heat treatment on the composite material block to obtain an aluminum-based composite material; wherein, the temperature of the smelting package during the vacuum gas atomization process is 830-860°C.

[0030] The present application prepares aluminum-based composite material powder by adopting vacuum air atomization technology, which is beneficial to the uniform distribution of reinforcing phase particles in the aluminum alloy fine-grained matrix, and is beneficial to reducing the content of impurities introduced into the aluminum-based composite material during the preparation process, thereby improving the purity of the aluminum-based composite material. At the same time, controlling the temperature of the smelting bag in the vacuum air atomization process within the above range is beneficial to controlling the particle size and morphology of the powder, and is also beneficial to improving the efficiency of atomization. Then, the spark plasma sintering technology is adopted, which is beneficial to processing the composite material powder into a dense block blank. Then, the microstructure and precipitated phase are regulated and controlled in combination with thermal deformation and heat treatment processes, which is beneficial to further refine the grains, control the organizational morphology, and improve the comprehensive mechanical properties of the prepared aluminum-based composite material.

[0031] In one embodiment of the present application, in the above step S1, the atomization pressure of vacuum air atomization is 1.5-8 MPa, and / or the intermediate package temperature of vacuum air atomization is 780-820°C, and / or the atomization medium of vacuum air atomization is argon; and / or the median particle size of the aluminum-based composite material powder is 15-30 μm, the nitrogen content is ≤100 ppm, and the oxygen content is ≤800 ppm.

[0032] Optimizing and controlling the vacuum gas atomization conditions within the above range is conducive to controlling the cooling rate and forming process of the powder, thereby improving the particle size and morphology of the powder. Controlling argon as the gas atomization medium can not only provide an inert protective environment and reduce powder oxidation, but also reduce costs. Controlling the particle size and impurity content of the powder is helpful to improve the density and purity of the aluminum-based composite material after sintering.

[0033] In one embodiment of the present application, in the above step S1, the mass fraction of the reinforced particles in the Al-reinforced particle master alloy block is 28% to 32%, and / or the median particle size of the reinforced particles in the Al-reinforced particle master alloy block is 0.8 to 5 μm.

[0034] It is preferred to control the mass fraction median particle size of the reinforcing particles in the Al-reinforced particle master alloy block within the above range, which helps to improve the dispersion state of the reinforcing particles in the alloy matrix during the powder metallurgy process, thereby improving the comprehensive performance of the aluminum-based composite material. The above-mentioned higher mass fraction of reinforcing particles can improve the modulus of the aluminum-based composite material, and the reasonable particle size distribution is conducive to the good combination of the reinforcing particles and the alloy matrix, reducing the occurrence of agglomeration, thereby improving the tensile strength and plasticity of the aluminum-based composite material.

[0035] In one embodiment of the present application, in the above step S2, the sintering temperature of spark plasma sintering is 420-550°C; and / or the sintering pressure of spark plasma sintering is 40-50MPa; and / or the holding time of spark plasma sintering is 5-30min; and / or the pulse current of spark plasma sintering is 600-800A.

[0036] It is preferred to control the conditions of spark plasma sintering within the above range, which is beneficial to improve the density of the aluminum-based composite material and the uniformity of the microstructure, and provide high-quality blanks for subsequent thermal deformation and heat treatment. Due to the presence of metal matrix and ceramic particles in the composite material, the electrical conductivity and thermal conductivity of the two are different, and the response to pulse current is also different. Too high a pulse current can easily lead to local overheating and abnormal grain growth, which has an adverse effect on the uniformity and performance of the organization. Too low a pulse current is not conducive to the generation of an appropriate amount of discharge plasma and Joule heating effect. It is preferred to control the parameters of the pulse current within the above range, which helps to generate appropriate discharge plasma and Joule heating effect, thereby promoting the melting and bonding of powder particles and improving sintering efficiency.

[0037] In one embodiment of the present application, in the above step S2, the density of the aluminum-based composite material block is 99.0% to 99.9%.

[0038] The density of the aluminum-based composite material block is preferably controlled within the above range, which is beneficial to reducing the probability of pores appearing in the aluminum-based composite material after sintering, thereby improving the tensile strength and plasticity of the aluminum-based composite material.

[0039] In one embodiment of the present application, in the above-mentioned step S3, the process of thermal deformation treatment includes: subjecting the aluminum-based composite material block to hot extrusion treatment to obtain a hot extrusion treated block; wherein, the temperature of the hot extrusion treatment is 360-420°C, and / or the extrusion speed of the hot extrusion treatment is 0.8-2m / s, and / or the hot extrusion ratio of the hot extrusion treatment is 8:1-30:1.

[0040] It is preferred to control the extrusion temperature within the above range, which is beneficial to inhibit the occurrence of dynamic recrystallization, so that the composite structure maintains a fibrous columnar crystal morphology, and further improves the strength and plasticity of the aluminum-based composite material. By controlling the extrusion speed and extrusion ratio of the hot extrusion process within the above range, it is beneficial to control the grain size and surface forming quality, thereby improving the comprehensive mechanical properties of the aluminum-based composite material.

[0041] In one embodiment of the present application, in the above step S3, the heat treatment process includes: subjecting the hot extruded block to a two-stage solution treatment and an aging treatment in sequence; the two-stage solution treatment includes a primary solution treatment and a secondary solution treatment in sequence; and / or the temperature of the primary solution treatment is 300-400°C, and the time of the primary solution treatment is 4-10 hours, wherein the purpose of the primary solution treatment is preferably to keep the temperature within the temperature range for a long time, thereby helping to eliminate the deformation stress in the hot extrusion structure, and can promote the precipitation of Al3 (Sc, Zr) particles, pin the grain boundaries, inhibit the occurrence of recrystallization during the subsequent heat treatment, and maintain the columnar crystal morphology of the grains. The temperature of the secondary solution treatment is preferably 460-480°C, and the time of the secondary solution treatment is 0.5-2 hours. The solution treatment at this temperature is conducive to promoting the dissolution of alloying elements, and controlling the temperature and time of the secondary solution treatment is conducive to promoting the grains not to recrystallize and grow. The preferred aging treatment temperature is 110-150° C. and the aging treatment time is 6-48 h, which helps to promote the precipitation of nano-scale precipitation phases under low temperature conditions, thereby improving the strength of the composite material.

[0042] By controlling the conditions of the two-stage solid solution treatment and the aging treatment within the above range, it is beneficial to regulate the formation and distribution of the precipitated phase in the composite material, especially by adding Zn element and trace amounts of Sc, Zr, and Er microalloying elements to the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, which, in combination with the above two-stage solid solution system, can optimize the microstructure of the material, refine the grains, inhibit recrystallization, and strengthen by aging, which can significantly improve the comprehensive mechanical properties, plasticity, and toughness of the composite material, and achieve the goal of preparing high-performance aluminum-based composite materials.

[0043] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0044] Example 1

[0045] An aluminum-based composite material comprises an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and TiB2 particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, wherein the mass of the TiB2 particles is 25wt% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; in terms of mass percentage, the component proportions of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix are: 15wt% of Zn element, 3.0wt% of Mg element, 1.2wt% of Cu element, 0.4wt% of Sc element, 0.2wt% of Zr element, 0.08wt% of Er element, and the remainder is Al element.

[0046] The specific preparation method is: the raw materials of Al-TiB2 intermediate alloy block with TiB2 content of 32%, pure Zn block, pure Mg block, Al-5Cu intermediate alloy block, Al-5Sc intermediate alloy block, Al-10Zr intermediate alloy block and Al-5Er intermediate alloy block are loaded into the melting ladle of vacuum gas atomization device according to the above-mentioned proportion, and the melting ladle is heated to 860°C to completely melt the raw materials. After insulation, the melt is transferred to the intermediate ladle for gas atomization to obtain aluminum-based composite material powder; wherein, the median particle size of TiB2 particles in the Al-TiB2 intermediate alloy block is 2μm, the temperature of the intermediate ladle is set to 800°C, the gas atomization pressure is set to 5MPa, and the gas atomization medium is argon.

[0047] Take 500g of the above-mentioned aluminum-based composite material powder and load it into a graphite mold with a diameter of 40mm; place the mold in a spark plasma sintering furnace and heat it to 500℃; after reaching the temperature, pressurize it to 50MPa with a current intensity of 800A, keep it at this temperature and pressure for 15min, then cool it down and reduce the pressure to room temperature and atmospheric pressure to obtain a pressed composite material block.

[0048] The above-mentioned pressed composite material block and hot extrusion die are placed in a resistance furnace and heated to 360°C. After keeping warm for 5 minutes, they are taken out and placed in a hot extruder; wherein, the extrusion ratio is set to 25:1, and the extrusion speed is set to 2mm / s. The profile obtained by hot extrusion is placed in a resistance furnace for two-stage solid solution treatment. The temperature of the first solid solution is set to 350°C, and the time of the first solid solution is 10h. Then the temperature is raised to 475°C for the second solid solution. The time of the second solid solution is 1h. The composite material profile is quickly taken out for quenching. The quenching medium is water at room temperature. The quenched composite material profile is subjected to aging treatment. The aging temperature is set to 120°C and the aging time is 24h to obtain an aluminum-based composite material. Among them, the organizational structure diagram of the TiB2 particle reinforced aluminum-based composite material powder after aerosol treatment is shown in the figure Figure 1As shown in the figure; (a) shows the surface morphology of the TiB2 particle reinforced aluminum matrix composite powder (secondary electron image); (b) shows the cross-sectional structure morphology of the TiB2 particle reinforced aluminum matrix composite powder. The structure diagram of the TiB2 particle reinforced aluminum matrix composite after thermal deformation and heat treatment is shown in the figure. Figure 2 As shown in the figure; (a) represents the hot extrusion structure morphology (backscattered electron image); (b) represents the hot extrusion structure orientation distribution map (IPF map); (c) represents the structure morphology after solution treatment (backscattered electron image); (d) represents the precipitation phase distribution map in the composite material after aging treatment.

[0049] Example 2

[0050] An aluminum-based composite material comprises an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and TiB2 particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, wherein the mass of the TiB2 particles is 15wt% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; in terms of mass percentage, the component proportions of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix are: 12wt% of Zn element, 3.6wt% of Mg element, 1.0wt% of Cu element, 0.2wt% of Sc element, 0.25wt% of Zr element, 0.1wt% of Er element, and the remainder is Al element.

[0051] The specific preparation method is: the raw materials of Al-TiB2 intermediate alloy block with TiB2 content of 32%, pure Zn block, pure Mg block, Al-5Cu intermediate alloy block, Al-5Sc intermediate alloy block, Al-10Zr intermediate alloy block and Al-5Er intermediate alloy block are loaded into the melting ladle of vacuum gas atomization device according to the above-mentioned proportion, and the melting ladle is heated to 860°C to completely melt the raw materials. After insulation, the melt is transferred to the intermediate ladle for gas atomization to obtain aluminum-based composite material powder; wherein, the median particle size of TiB2 particles in the Al-TiB2 intermediate alloy block is 0.8μm, the temperature of the intermediate ladle is set to 780°C, the gas atomization pressure is set to 2.7MPa, and the gas atomization medium is argon.

[0052] Take 500g of the above-mentioned aluminum-based composite material powder and load it into a graphite mold with a diameter of 40mm; place the mold in a spark plasma sintering furnace and raise the temperature to 520℃; after reaching the temperature, pressurize it to 50MPa with a current intensity of 750A, keep it at this temperature and pressure for 20min, then cool it down and reduce the pressure to room temperature and atmospheric pressure to obtain a pressed composite material block.

[0053] The pressed composite material block and the hot extrusion die are placed in a resistance furnace and heated to 380°C. After keeping warm for 5 minutes, they are taken out and placed in a hot extruder; wherein, the extrusion ratio is set to 16:1 and the extrusion speed is set to 1mm / s. The hot extruded profile is placed in a resistance furnace for two-stage solid solution treatment, the temperature of the first solid solution is set to 300°C, the time of the first solid solution is 6h, and then the temperature is raised to 475°C for the second solid solution, the time of the second solid solution is 0.5h, and the composite material profile is quickly taken out for quenching, the quenching medium is room temperature water, and the quenched composite material profile is subjected to aging treatment, the aging temperature is set to 110°C, and the aging time is 48h to obtain an aluminum-based composite material.

[0054] Example 3

[0055] An aluminum-based composite material comprises an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and TiB2 particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, wherein the mass of the TiB2 particles is 10wt% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; in terms of mass percentage, the component proportions of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix are: 10wt% of Zn element, 3.0wt% of Mg element, 1.6wt% of Cu element, 0.4wt% of Sc element, 0.1wt% of Zr element, 0.06wt% of Er element, and the remainder is Al element.

[0056] The specific preparation method is: the raw materials of Al-TiB2 intermediate alloy block with TiB2 content of 32%, pure Zn block, pure Mg block, Al-5Cu intermediate alloy block, Al-5Sc intermediate alloy block, Al-10Zr intermediate alloy block and Al-5Er intermediate alloy block are loaded into the melting ladle of vacuum gas atomization device according to the above-mentioned proportion, and the melting ladle is heated to 840°C to completely melt the raw materials. After insulation, the melt is transferred to the intermediate ladle for gas atomization to obtain aluminum-based composite material powder; wherein, the median particle size of TiB2 particles in the Al-TiB2 intermediate alloy block is 5μm, the temperature of the intermediate ladle is set to 820°C, the gas atomization pressure is set to 3.0MPa, and the gas atomization medium is argon.

[0057] Take 500g of the above-mentioned aluminum-based composite material powder and load it into a graphite mold with a diameter of 40mm; place the mold in a spark plasma sintering furnace and raise the temperature to 550℃; after reaching the temperature, pressurize it to 40MPa with a current intensity of 700A, keep it at this temperature and pressure for 5min, then cool it down and reduce the pressure to room temperature and atmospheric pressure to obtain a pressed composite material block.

[0058] The pressed composite material block and the hot extrusion die are placed in a resistance furnace and heated to 420°C. After keeping warm for 5 minutes, they are taken out and placed in a hot extruder; wherein, the extrusion ratio is set to 8:1 and the extrusion speed is set to 1mm / s. The hot extruded profile is placed in a resistance furnace for two-stage solid solution treatment, the temperature of the first solid solution is set to 400°C, the time of the first solid solution is 10h, and then the temperature is raised to 470°C for the second solid solution, the time of the second solid solution is 2h, and the composite material profile is quickly taken out for quenching, the quenching medium is room temperature water, and the quenched composite material profile is subjected to aging treatment, the aging temperature is set to 120°C, and the aging time is 12h to obtain an aluminum-based composite material.

[0059] Example 4

[0060] An aluminum-based composite material comprises an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and TiB2 particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, wherein the mass of the TiB2 particles is 20wt% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; in terms of mass percentage, the component proportions of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix are: 15wt% of Zn element, 2.4wt% of Mg element, 1.6wt% of Cu element, 0.1wt% of Sc element, 0.4wt% of Zr element, 0.04wt% of Er element, and the remainder is Al element.

[0061] The specific preparation method is: the raw materials of Al-TiB2 intermediate alloy block with TiB2 content of 32%, pure Zn block, pure Mg block, Al-5Cu intermediate alloy block, Al-5Sc intermediate alloy block, Al-10Zr intermediate alloy block and Al-5Er intermediate alloy block are loaded into the melting ladle of vacuum gas atomization device according to the above-mentioned proportion, and the melting ladle is heated to 830°C to completely melt the raw materials. After insulation, the melt is transferred to the intermediate ladle for gas atomization to obtain aluminum-based composite material powder; wherein, the median particle size of TiB2 particles in the Al-TiB2 intermediate alloy block is 2μm, the temperature of the intermediate ladle is set to 800°C, the gas atomization pressure is set to 1.5MPa, and the gas atomization medium is argon.

[0062] Take 500g of the above-mentioned aluminum-based composite material powder and load it into a graphite mold with a diameter of 40mm; place the mold in a spark plasma sintering furnace and raise the temperature to 470℃; after reaching the temperature, pressurize it to 45MPa with a current intensity of 600A, keep it at this temperature and pressure for 20min, then cool it down and reduce the pressure to room temperature and atmospheric pressure to obtain a pressed composite material block.

[0063] The pressed composite material block and the hot extrusion die are placed in a resistance furnace and heated to 380°C. After keeping warm for 5 minutes, they are taken out and placed in a hot extruder; wherein, the extrusion ratio is set to 30:1 and the extrusion speed is set to 0.8mm / s. The profile obtained by hot extrusion is placed in a resistance furnace for two-stage solid solution treatment, the temperature of the first solid solution is set to 350°C, the time of the first solid solution is 3h, and then the temperature is raised to 490°C for the second solid solution, the time of the second solid solution is 1h, and the composite material profile is quickly taken out for quenching, the quenching medium is room temperature water, and the quenched composite material profile is subjected to aging treatment, the aging temperature is set to 150°C, and the aging time is 6h to obtain an aluminum-based composite material.

[0064] Example 5

[0065] An aluminum-based composite material comprises an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and TiB2 particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, wherein the mass of the TiB2 particles is 10wt% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; in terms of mass percentage, the component proportions of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix are: 11.5wt% of Zn element, 2.4wt% of Mg element, 1.5wt% of Cu element, 0.1wt% of Sc element, 0.2wt% of Zr element, 0.1wt% of Er element, and the remainder is Al element.

[0066] The specific preparation method is: the raw materials of Al-TiB2 intermediate alloy block with TiB2 content of 32%, pure Zn block, pure Mg block, Al-5Cu intermediate alloy block, Al-5Sc intermediate alloy block, Al-10Zr intermediate alloy block and Al-5Er intermediate alloy block are loaded into the melting ladle of vacuum gas atomization device according to the above-mentioned proportion, and the melting ladle is heated to 860°C to completely melt the raw materials. After heat preservation, the melt is transferred to the intermediate ladle for gas atomization to obtain aluminum-based composite material powder; wherein, the median particle size of TiB2 particles in the Al-TiB2 intermediate alloy block is 2μm, the temperature of the intermediate ladle is set to 820°C, the gas atomization pressure is set to 10MPa, and the gas atomization medium is argon.

[0067] Take 500g of the above-mentioned aluminum-based composite material powder and load it into a graphite mold with a diameter of 40mm; place the mold in a spark plasma sintering furnace and heat it to 490℃; after reaching the temperature, pressurize it to 45MPa with a current intensity of 700A, keep it at this temperature and pressure for 15min, then cool it down and reduce the pressure to room temperature and atmospheric pressure to obtain a pressed composite material block.

[0068] The pressed composite material block and the hot extrusion die are placed in a resistance furnace and heated to 400°C. After keeping warm for 5 minutes, they are taken out and placed in a hot extruder; wherein, the extrusion ratio is set to 16:1 and the extrusion speed is set to 1.6mm / s. The profile obtained by hot extrusion is placed in a resistance furnace for two-stage solid solution treatment, the temperature of the first solid solution is set to 400°C, the time of the first solid solution is 6h, and then the temperature is raised to 485°C for the second solid solution, the time of the second solid solution is 1h, and the composite material profile is quickly taken out for quenching, the quenching medium is room temperature water, and the quenched composite material profile is subjected to aging treatment, the aging temperature is set to 120°C, and the aging time is 36h to obtain an aluminum-based composite material.

[0069] Example 6

[0070] An aluminum-based composite material comprises an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and TiB2 particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, wherein the mass of the TiB2 particles is 20wt% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; in terms of mass percentage, the component proportions of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix are: 13.5wt% of Zn element, 3.2wt% of Mg element, 1.0wt% of Cu element, 0.25wt% of Sc element, 0.15wt% of Zr element, 0.08wt% of Er element, and the remainder is Al element.

[0071] The specific preparation method is: the raw materials of Al-TiB2 intermediate alloy block with TiB2 content of 32%, pure Zn block, pure Mg block, Al-5Cu intermediate alloy block, Al-5Sc intermediate alloy block, Al-10Zr intermediate alloy block and Al-5Er intermediate alloy block are loaded into the melting ladle of vacuum gas atomization device according to the above-mentioned proportion, and the melting ladle is heated to 830°C to completely melt the raw materials. After insulation, the melt is transferred to the intermediate ladle for gas atomization to obtain aluminum-based composite material powder; wherein, the median particle size of TiB2 particles in the Al-TiB2 intermediate alloy block is 2μm, the temperature of the intermediate ladle is set to 820°C, the gas atomization pressure is set to 8MPa, and the gas atomization medium is argon.

[0072] Take 500g of the above-mentioned aluminum-based composite material powder and load it into a graphite mold with a diameter of 40mm; place the mold in a spark plasma sintering furnace and heat it to 500℃; after reaching the temperature, pressurize it to 40MPa with a current intensity of 800A, keep it at this temperature and pressure for 30min, then cool it down and reduce the pressure to room temperature and atmospheric pressure to obtain a pressed composite material block.

[0073] The pressed composite material block and the hot extrusion die are placed in a resistance furnace and heated to 380°C. After keeping warm for 5 minutes, they are taken out and placed in a hot extruder; wherein, the extrusion ratio is set to 25:1 and the extrusion speed is set to 2mm / s. The hot extruded profile is placed in a resistance furnace for two-stage solid solution treatment, the temperature of the first solid solution is set to 300°C, the time of the first solid solution is 6h, and then the temperature is raised to 485°C for the second solid solution, the time of the second solid solution is 2h, and the composite material profile is quickly taken out for quenching, the quenching medium is room temperature water, and the quenched composite material profile is subjected to aging treatment, the aging temperature is set to 120°C, and the aging time is 18h to obtain an aluminum-based composite material.

[0074] Example 7

[0075] The difference from Example 1 is that the Al-TiB2 master alloy block contains 28%, so that the mass of TiB2 particles in the aluminum-based composite material is 10wt% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix.

[0076] Example 8

[0077] The difference from Example 1 is that the Al-TiB2 intermediate alloy block accounts for 32%, so that the mass of TiB2 particles in the aluminum-based composite material is 15wt% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, and finally an aluminum-based composite material is obtained.

[0078] Example 9

[0079] The difference from Example 1 is that the median particle size of the TiB2 particles in the Al-TiB2 master alloy block is 0.8 μm, and an aluminum-based composite material is finally obtained.

[0080] Example 10

[0081] The difference from Example 1 is that the median particle size of the TiB2 particles in the Al-TiB2 master alloy block is 5 μm, and an aluminum-based composite material is finally obtained.

[0082] Embodiment 11

[0083] The difference from Example 1 is that the median particle size of the TiB2 particles in the Al-TiB2 master alloy block is 6 μm, and an aluminum-based composite material is finally obtained.

[0084] Example 12

[0085] The difference from Example 1 is that the temperature of the smelting ladle during the vacuum gas atomization process is 830° C., and an aluminum-based composite material is finally obtained.

[0086] Example 13

[0087] The difference from Example 1 is that the temperature of the smelting ladle during the vacuum gas atomization process is 850° C., and an aluminum-based composite material is finally obtained.

[0088] Embodiment 14

[0089] The difference from Example 1 is that the extrusion ratio is set to 8:1, and an aluminum-based composite material is finally obtained.

[0090] Embodiment 15

[0091] The difference from Example 1 is that the extrusion ratio is set to 30:1, and an aluminum-based composite material is finally obtained.

[0092] Example 16

[0093] The difference from Example 1 is that the extrusion ratio is set to 7:1, and an aluminum-based composite material is finally obtained.

[0094] Comparative Example 1

[0095] The difference from Example 1 is that the aluminum-based composite material does not contain TiB2 particles, and the aluminum-based composite material is finally obtained.

[0096] Comparative Example 2

[0097] The difference from Example 1 is that the aluminum-based composite material is prepared by an in-situ autogenous method (for details, refer to the patent with the authorization announcement number CN 113755726 B).

[0098] Comparative Example 3

[0099] The difference from Example 1 is that the temperature of the smelting ladle during the vacuum gas atomization process is 810° C., and an aluminum-based composite material is finally obtained.

[0100] Comparative Example 4

[0101] The difference from Example 1 is that the temperature of the smelting ladle during the vacuum gas atomization process is 880° C., and an aluminum-based composite material is finally obtained.

[0102] Performance Testing:

[0103] Tensile strength: GB / T228.1-2021 standard is used to measure the tensile strength of aluminum-based composite materials.

[0104] Elastic modulus: GB / T22315-2008 tensile elastic modulus of metal materials (static method) was used to measure the elastic modulus of aluminum-based composite materials.

[0105] The average grain size of aluminum-based composite materials and the average grain size of equiaxed crystal structures: The average grain size is calculated using EBSDIPF images according to the ASTM E2627 standard, and the number of grains in each image is not less than 2000.

[0106] The aluminum-based composite materials prepared in the examples and comparative examples were subjected to tensile tests to test the tensile strength and elastic modulus of the composite materials, and the average grain size of the aluminum-based composite materials and the average grain size of the equiaxed crystal structure were tested. The results are shown in Table 1 below.

[0107] Table 1

[0108]

[0109]

[0110] Among them, the alloy melt of Comparative Example 3 cannot complete the atomization process due to its high viscosity and cannot be formed.

[0111] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0112] The aluminum-based composite material of the present application is beneficial to improve the tensile strength and elastic modulus of the aluminum-based composite material by introducing reinforcing particles as reinforcing phases in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix, so that the elastic modulus of the aluminum-based composite material is improved by 10GPa to 20GPa, and the combination of lightweight and high performance is achieved. Specifically, on the one hand, the high melting point and high modulus characteristics of the reinforcing particles, as well as their dispersed distribution inside the matrix grains and at the grain boundaries, effectively inhibit the growth of the matrix grains during thermal deformation and heat treatment, and at the same time, a large number of reinforcing particles hinder the movement of dislocations during deformation, thereby improving the tensile strength (tensile strength is increased to 750MPa to 850MPa) and elastic modulus of the aluminum-based composite material. On the other hand, the addition of Zn elements exceeding the traditional 7xxx series aluminum alloy and trace amounts of Sc, Zr, and Er microalloying elements in the alloy matrix can play the role of grain refinement, recrystallization inhibition, and aging strengthening, thereby significantly improving the comprehensive mechanical properties of the aluminum-based composite material.

[0113] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An aluminum-based composite material, characterized in that: The aluminum-based composite material comprises an Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix and reinforcement particles dispersed in the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; Wherein, the mass of the reinforcing particles is 10% to 25% of the mass of the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix; In terms of mass percentage, the Al-Zn-Mg-Cu-Sc-Zr-Er alloy matrix includes 10wt% to 15wt% of Zn element, 2.4wt% to 3.6wt% of Mg element, 1.0wt% to 1.6wt% of Cu element, 0.1wt% to 0.4wt% of Sc element, 0.1wt% to 0.4wt% of Zr element, and 0.04wt% to 0.1wt% of Er element; Wherein, the reinforcing particles are selected from any one or more of SiC, TiC, AlN, ZrB2 and TiB2 particles.

2. The aluminum-based composite material according to claim 1, characterized in that: The average grain size of the aluminum-based composite material is 2-3 μm.

3. The aluminum-based composite material according to claim 1 or 2, characterized in that: At 20-30° C., the tensile strength of the aluminum-based composite material is 750-850 MPa, and / or the elastic modulus of the aluminum-based composite material is 85-95 GPa.

4. A method for preparing the aluminum-based composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, vacuum gas atomizing the Al-reinforced particle master alloy block, the pure Zn block, the pure Mg block, the Al-5Cu master alloy block, the Al-5Sc master alloy block, the Al-10Zr master alloy block, and the Al-5Er master alloy block according to the proportion of claim 1 to obtain an aluminum-based composite material powder; Step S2, spark plasma sintering the aluminum-based composite material powder to obtain an aluminum-based composite material block; Step S3, sequentially subjecting the composite material block to thermal deformation treatment and heat treatment to obtain the aluminum-based composite material; Wherein, the temperature of the smelting ladle during the vacuum air atomization process is 830-860°C.

5. The preparation method according to claim 4, characterized in that: In the step S1, the atomization pressure of the vacuum air atomization is 1.5 to 8 MPa, and / or the tundish temperature of the vacuum air atomization is 780 to 820°C, and / or the atomization medium of the vacuum air atomization is argon; and / or the median particle size of the aluminum-based composite material powder is 15 to 30 μm, the nitrogen content is ≤100 ppm, and the oxygen content is ≤800 ppm.

6. The preparation method according to claim 4 or 5, characterized in that: In the step S1, the mass fraction of the reinforced particles in the Al-reinforced particle master alloy block is 28% to 32%, and / or the median particle size of the reinforced particles in the Al-reinforced particle master alloy block is 0.8 to 5 μm.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S2, the sintering temperature of the spark plasma sintering is 420-550°C; and / or the sintering pressure of the spark plasma sintering is 40-50MPa; and / or the holding time of the spark plasma sintering is 5-30min; and / or the pulse current of the spark plasma sintering is 600-800A.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In the step S2, the density of the aluminum-based composite material block is 99.0% to 99.9%.

9. The preparation method according to any one of claims 4 to 8, characterized in that: In step S3, the process of the thermal deformation treatment includes: subjecting the aluminum-based composite material block to hot extrusion treatment to obtain a hot extrusion treatment block; wherein the temperature of the hot extrusion treatment is 360 to 420°C, and / or the extrusion speed of the hot extrusion treatment is 0.8 to 2 m / s, and / or the hot extrusion ratio of the hot extrusion treatment is 8:1 to 30:

1.

10. The preparation method according to any one of claims 4 to 9, characterized in that: In step S3, the heat treatment process includes: The hot extrusion treated block is subjected to a double-stage solution treatment and an aging treatment in sequence; The two-stage solution treatment includes a primary solution treatment and a secondary solution treatment performed sequentially; and / or the temperature of the primary solution treatment is 300-400° C., and the time of the primary solution treatment is 4-10 hours; and / or the temperature of the secondary solution treatment is 460-480° C., and the time of the secondary solution treatment is 0.5-2 hours; And / or the temperature of the aging treatment is 110-150° C., and the time of the aging treatment is 6-48 hours.

Citation Information

Patent Citations

  • Ultra-high-strength and ultra-fine-grain TiB2 reinforced Al-Zn-Mg-Cu composite material and preparation method thereof

    CN111500908A

  • High-modulus, high-strength and high-toughness aluminum-based composite material and preparation method thereof

    CN113755726A

  • A high-modulus, high-strength, and high-toughness aluminum-based composite material and its preparation method

    CN113755726B

  • High-elongation and high-modulus TiB2 particle reinforced aluminum-based composite material and preparation method thereof

    CN114032429A

Cited By

  • Crack-resistant high-toughness rare earth aluminum alloy and preparation method, aluminum alloy part and additive manufacturing method, and application

    CN122542886A